Resource Aware Application for Mobile Device In An Ad Hoc Wireless Network Environment - Saaya, Zurina; Roslan, Irda; Ramly, Marliza (2010)
Ad hoc wireless networks can be applied in a collaborative computing in which the requirements of a temporary communication infrastructure for quick communication with minimal configuration between a group of people in a conference or gathering. The main purpose of this research is to develop an application that allows mobile nodes in a collaborative environment to share files among nodes. For this project, the application will be implemented on nodes in an ad hoc wireless network that have a strong incentive to collaborate and share resources. This paper presents the results of our preliminary study which are based on the previous research. It is divided into five sections where in the first section is an introduction of ad-hoc wireless network, then in the next section is regarding motivation of doing research in this area. In section four and five, the paragraphs focused on the evaluation for Mobile Ad Hoc Networking and related works respectively.